ADAPTASI PROGRAM MICROTEACHING BAGI CALON GURU BAHASA INDONESIA PADA MASA PANDEMI COVID-19 - Main Sufanti, Dini Restiyanti Pratiwi, Khabib Sholeh (Universitas Muhammadiyah Surakarta, 2022)
This study aimed to describe the implementation of a microteaching program to pre-service Bahasa Indonesia teachers during the Covid-19 pandemic, the advantages of the program, and its weaknesses. Data related to the changes in the program when facing a pandemic, advantages of program changes, and weaknesses. Data obtained from the Microteaching course in the Indonesian Language and Literature Department in The Universitas Muhammadiyah Surakarta. Microteaching in the semester of 2019/2020 amounted to 209 students. Data were from observation techniques, questionnaires, and document analysis. The sample was selected randomly. Triangulation techniques and methods validated the data, the interactive term used for data analysis. The results of this study are as follows. (1) To deal with the Covid-19, there are no changes in the core stages of Microteaching, but it needs some adaptations to the implementation, such as learning tools, teaching practices, observation activities, and assessments. (2) The advantages of adapting this program are students have flexible time and place of practice, improved information technology capabilities, and the student experience varies as they can write more stories. (3) The weaknesses of the adaptation of this program are the workload of lecturers increases, student learning burden increases, limited interaction, and network problems